Evaluasi Kesehatan Keuangan Melalui Analisis Rasio Keuangan: Studi Kasus PT Semen Indonesia (Persero) Tbk - Assandri, Novita; Kusumandari, Nafia (Amsir Management Journal, 2023)
This study aims to analyze the financial performance of PT Semen Indonesia (Persero) Tbk in the 2021-2022 period. The analytical method used is using the ratio of liquidity, solvency, activity, and profitability. The results showed that the liquidity ratio with the calculation indicators using the Current Ratio, Quick Ratio, and Cash Ratio. The Current Ratio, Quick Ratio, and Cash Ratio show "not good" results compared to the industry average. Solvability ratios with calculation indicators, namely Debt to debt-to-asset ratio, Debt to Equity Ratio, Long Term Debt to Equity Ratio. Debt to Asset Ratio and Long Term Debt to Equity Ratio which shows " not good" results when compared to the industry average. Meanwhile, the Equity Ratio showed "good" results. Activity ratios with indicators for calculations use Receivable Turn Over, Inventory Turn Over, and Working Capital Turn Over. Receivable Turn Over, Inventory Turn Over, and Working Capital Turn Over show "not good" results. Profitability ratios with indicators of Net Profit Margin, Return on Investment, and Return on Equity. Net Profit Margin, Return on Investment and Return on Equity show "not good" results